The Effect of Transformational Leadership and Organizational Culture on Employee Performance with Work Environment as Mediation Variable (Study at PT Japura Inti Pangan) - Cindy Chintya Aristarini; Slamet Riyadi; Abdul Halik (International Journal of Economics (IJEC), 2024)
Employee performance is a result of effort, perception and task ability given to achieve organizational success with the level and mastery of skills possessed by subordinates with the responsibilities given. There are several factors that affect the level of performance of an employee including transformational leadership, organizational culture, and work environment. The approach used is quantitative withthe data collection method using a questionnaire. In this study the population was all employees of the marketing division of PT Japura Inti Pangan with a saturated sampling technique of 45 employees. The analysis technique used is Path Analysis through SmartPLS version 4 software. The measurements used include outer model measurements, mediation tests and inner models. The field findings show that Transformational Leadership significant effect on the work environment with a coefficient value of 1,195 pvalue 0.000. Organizational culture has no significant effect on the work environment with a coefficient of -0.382 p-value 0.000. The work environment has a significant effect on employee performance with a p-value of 0.003 for a coefficient of 0.601. Environment work is able to mediate between the influence of transformational leadership on employee performance. While the work environment has not been able to mediate between the influence of organizational culture on employee performance.